AUTOMASI PENJADWALAN WORK FROM OFFICE (WFO) - Putu Arya Dharma Kesuma; Ngurah Agus Sanjaya ER; I Ketut Gede Suhartana (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
Work From Office (WFO) scheduling at PT Digjaya Digital Group is a major challenge considering the limited space capacity and number of employees, especially PKL participants who often exceed the available capacity. Manual scheduling is time-consuming and prone to errors, especially when there are additional PKL participants. This automatic scheduling generator program is designed to overcome these problems, with features including capacity that allows adjustments to the number of employees each day according to the available capacity. The implementation results show that this program is able to reduce manual errors, ensure fair schedule rotation, and maximize the efficiency of office space usage. This system is expected to support a comfortable and safe working environment, as well as increase efficiency in managing WFO scheduling in the company.